Avaliação estatística dos parâmetros operacionais das unidades de regeneração de ácido clorídrico da Usiminas - Alex Souza Ferreira (2009)
Operational parameters of the hydrochloric acid regeneration process and iron oxide production of the USIMINAS industrial plant were evaluated aiming to: (i) identify those statistically significant both for the quality of the oxide produced as for the generation of gases, and (ii) to develop statistical models that allow a satisfactory assessment of the process. Initially a reduction in the number of parameters was tried through statistical analysis of historical data collected in the plant 3, but the study was inconclusive due to the small number of available data. For this reason, the study focused only the stage of production of iron oxide and a full 24 factorial design was done with the parameters temperature, feed flow, pressure and relation air/gas (lambda). Tests were performedat the USIMINAS plant 1. Samples of the oxide produced were collected at the exit of the furnace and analyzed in the laboratory in order to quantify the contents levels of chlorine, iron oxide, MnO, SiO2, humidity and pH. The data were analyzed using the software STATISTICA. It was found that parameters temperature and feed flow have shown greater influence on the final composition of iron oxide, for the conditions investigated, and that an iron oxide meeting the quality condition required by customerscould be produced thus operating the plant at the superior limits studied for these parameters, independently of the remaining parameters evaluated. It was also found that the quality of the used acid (which is produced in pickling lines for the various types of steel produced by the company) that was fed to the regeneration plant interfered mainly on the contents of SiO2 and MnO of the produced oxide. Based on the results obtained in the study, new conditions have been proposed for industrialprocessing of used acid that feed regeneration furnace to improve the control of the contents of the SiO2 and MnO in the produced oxide.